Power Weighted Versions of Bennett, Alpert, and Goldstein’s S - Matthijs J. Warrens (Journal of Mathematics)
A weighted version of Bennett, Alpert, and Goldstein’s S, denoted by Sr, is studied. It is shown that the special cases of Sr are often ordered in the same way. It is also shown that many special cases of Sr tend to produce values close to unity, especially when the number of categories of the rating scale is large. It is argued that the application of Sr as an agreement coefficient is not without difficulties.